Generalized free Gaussian white noise - Othman, Hakeem (International Journal of Advanced Mathematical Sciences, 2016)
Based on an adequate new Gel'fand triple,Â  we construct the infinite dimensional free Gaussian white noise measure \(μ\) using the Bochner-Minlos theorem. Next, we give the chaos decomposition of an \(L^{2}\) space with respect to the measure \(μ\).